Construção enxuta: análise e aplicação dos princípios em empresa de pré-moldados - Freisleben, Patrícia Luiza Moscon (2014)
The precast elements are considered technological innovation in Civil Construction and every day get more importance in the face of an increasingly demanding market with the final product quality, imposing further limit to deadlines. Therefore the improvement of construction techniques and materials used is required. The manufacturing process of pre molded parts in building aims to optimize the time in production of the parts, lower costs and the complete elimination of wastage, also seeking the reduction of the workforce. The objective of this study was to analyze the manufacture of precast pillars of a company and, from this analysis hold a current Value Stream Map of this process. From this map it was possible to analyze the critical points of the process, in sequence from the point of view of Lean Construction to point out improvements, based on its principles, which result in greater efficiency in production. These improvements have been implemented in the new Value Stream Map which shows that by using the improvements suggested the company could achieve productivity gains, cost savings and eliminate most waste, both in manpower as time and materials.